Psychotherapy Research Domain Criteria: functional mechanisms of treatment and a basic theory of the mind - Rohlfing, Nico; Pum, Martin; Bonnet, Udo; Koelkebeck, Katja; Scherbaum, Norbert (Frontiers in Psychiatry, 2025)
The Research Domain Criteria (RDoC) approach is a tipping point in psychotherapy and introduces a new development in the treatment of mental disorders. The linking of clinical syndromes with their biological foundation shifts the emphasis of research and methodology on biology and increases the falsifiability of therapy schools, trends, and paradigms in psychotherapy. Interventions are not exclusively assessed according to their efficacy anymore; they focus on biological mechanisms and aim to alter them in an evidence-based way. At the same time, research benefits from the clinical expertise of experienced practitioners and proven treatment concepts. With this heterogeneity and with the decline of diagnosis-specific treatment, a vacuum occurs with respect to a basic theory on the functionality of the mind and the central approach for treatment. The mind can be assessed precisely by biologically based functional mechanisms. Needs could be moved into the center of treatment and their neural mechanisms, which overlap with addiction and reward processing, are the interface between universally valid or nomothetic processes and an individualized idiographic treatment. The RDoC approach will prospectively lead to a huge integration of proven treatment concepts to develop innovative evidence-based interventions and a basic theory of the mind in the sense of a universally valid neuropsychotherapy. The rationale was to define a central approach to and a RDoC perspective on psychotherapy.